2020
DOI: 10.1371/journal.pone.0234722
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of machine learning models for predicting outcomes of stroke with structured data

Abstract: Background and purpose Machine learning (ML) has attracted much attention with the hope that it could make use of large, routinely collected datasets and deliver accurate personalised prognosis. The aim of this systematic review is to identify and critically appraise the reporting and developing of ML models for predicting outcomes after stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
118
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(124 citation statements)
references
References 40 publications
6
118
0
Order By: Relevance
“…Moreover, anonymity and systematic bias elimination should be enforced. As an automatic medical screening system based on pervasive data, it has been shown that such frameworks are prone to implicit machine learning bias during data collection or training phases [69][70][71]. Black-box methods should be avoided, as they are known to be vulnerable to adversarial attacks and produce unexplainable distributional representations [72,73].…”
Section: Ethical and Privacy Concernsmentioning
confidence: 99%
“…Moreover, anonymity and systematic bias elimination should be enforced. As an automatic medical screening system based on pervasive data, it has been shown that such frameworks are prone to implicit machine learning bias during data collection or training phases [69][70][71]. Black-box methods should be avoided, as they are known to be vulnerable to adversarial attacks and produce unexplainable distributional representations [72,73].…”
Section: Ethical and Privacy Concernsmentioning
confidence: 99%
“…At present, there is a limited number of systematic reviews regarding the reporting and methodological quality of ML-based prediction model studies and their risks of bias. [32][33][34] In this systematic review, we will review across all medical fields, the current use of ML techniques in prediction model development, validation and updating studies, the methodological conduct and risks of bias using PROBAST, and the adherence to the reporting guideline using TRIPOD. Particularly, we will assess the extent to which risks of bias and reporting of ML-based prediction model studies match the current recommendations from TRIPOD and PROBAST, 22 and the implications of these results to update or extend them to TRIPOD-ML and PROBAST-ML.…”
Section: Discussionmentioning
confidence: 99%
“…Applicability of included studies was not assessed as our study was not concerned with a specific application of AI predictive models. In lieu of specific reporting standards for AI studies at the time of study conception 24 , we assessed the reporting quality of multivariable predictive modelling studies using an adaptation of Wang et al’s 25 modified TRIPOD statement 26 for AI models (Additional file 3). For all other studies, we summarised the study methodology, including data sources, application of AI, and validation methods, as well as the key findings of the study.…”
Section: Methodsmentioning
confidence: 99%